HANEFÎ MEZHEBİNİN KURUCU İMAMLARI ARASINDAKİ KİŞİSEL İLİŞKİLER - Ferhat Koca (İslami İlimler Dergisi)
The Personel Relations and Some Weaknesses Between Abû Hanîfa and His Students Who Are the Founder Imams of the Hanafî School Hanafi school whose name is attributed to Abû Hanîfa, today one of the four living law (fiqh) schools, is a secret (mazhab) established as collectively by Abû Hanîfa and his students and friends (ashâb-i Abî Hanîfa). Among Abû Hanîfa’s friends Abû Yusuf, Muhammad b. Hasan al-Shaybânî, Zufar and Hasan b. Ziyâd made the big contributions with their works and their activities in carrying out in institunalization and advancement of this school. In this article, we are dealing with the personel relations and some weaknesses between Abû Hanîfa and his students who are the founder imams of the Hanafî School with some historical examples.